Right to life under article 5(1) of Federal Constitution: the need for a dynamic interpretation / Nur Alia A.Rahman, Abdullah Abbas Abdul Munir and Nur Samiah Edruce - A.Rahman, Nur Alia; Abdul Munir, Abdullah Abbas; Edruce, Nur Samiah (Faculty of Law, 2011)
This legal research is conducted with an aim to study and analyse the meaning and ambit on right to life under Article 5(1)l of the Federal Constitution. To this date, no clear determination on the jurisprudence on the scope of this right by the Malaysian Court. Therefore, this work will focus on the deficiency on the interpretation of "life" in Malaysia as compared to the dynamic interpretation in India. The scope of this legal research is on interpretation on right to life under Article 5(1). To determine the meaning and scope of right to life, it is also vital to understand the principles on rules of interpretation of the constitution. With that, the research too explores the rules on interpretation of the constitution and the attitude adopted by the Malaysian judges when interpreting them. Further, to ensure that constitutional provision is construed independently and accordingly especially when interpreting provision on fundamental rights, it is essential to make sure that the judiciary body is independent. Thus, this research also involves the analysis on the independence of the Malaysian Judiciary.